Framework to assist investment portfolio generation for financial sector - Breno Barros Telles do Carmo; Pablo Picasso Morais de Medeiros; Thomas Edson Espíndola Gonçalo; Gabriela Colaço Correia (Exacta)
Several variables are influencing the financial performance of listed companies in the stock exchange, making the choice of an ideal investment portfolio complex. Multicriteria decision support methods emerge as a potential tool to support the investor in the asset selection process. Thus, this paper proposes a framework to assist investors in generating an investment portfolio in financial sector companies considering the fundamentalist analysis approach. Based on selected investors, the study defined the appropriate minimum performance filters, criteria, and weights for stock selection in the financial sector. The portfolio was established based on investor constraints using the PROMETHEE V method. As a subsequent step, an entire linear programming model was implemented to define, given the available budget, the amount of capital to be allocated to each asset of the portfolio. Compared to other publications, the proposed model and assembling the stocks portfolio proposes capital allocation based on previously defined restrictions. Also, the research provides investors with a clear and accurate method for selecting a stock portfolio and allowing customization of the model.